2007
DOI: 10.1590/s1516-35982007000100027
|View full text |Cite
|
Sign up to set email alerts
|

Teores de proteína bruta para bovinos alimentados com feno de capim-tifton 85: parâmetros ruminais, eficiência de síntese microbiana e degradabilidade in situ

Abstract: Avaliou-se o efeito da deficiência de PB na dieta sobre a eficiência de síntese microbiana e a degradabilidade in situ da MS e FDN em novilhos mestiços. Os tratamentos consistiram de dietas compostas de feno de tifton 85 (FN) suplementadas com uréia (FNUR), farelo de soja (FNFS) e farelo de glúten de milho- 60 (FNGL). Foram utilizados oito novilhos canulados no rúmen e no duodeno, distribuídos em dois quadrados latinos 4 x 4. O pH e a concentração de nitrogênio não-amoniacal (N-NH3) foram mensurados no fluido … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
1
12

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 26 publications
1
2
1
12
Order By: Relevance
“…The estimated values of microbial efficiency expressed in relation to RDOM and RDTC for the hay diet were greater than those obtained by Silva et al (2007), working with Tifton hay supplemented with soybean meal, among the different nitrogen sources evaluated, but lower than the results reported by Berchielli et al (1995a), who evaluated different markers, including DAPA, and different roughage:concentrate ratios, and Cabral et al (2008), who evaluated different forages. These same authors, utilizing corn silage, reported slightly greater efficiencies than the results obtained in the current study.…”
Section: Resultscontrasting
confidence: 70%
See 1 more Smart Citation
“…The estimated values of microbial efficiency expressed in relation to RDOM and RDTC for the hay diet were greater than those obtained by Silva et al (2007), working with Tifton hay supplemented with soybean meal, among the different nitrogen sources evaluated, but lower than the results reported by Berchielli et al (1995a), who evaluated different markers, including DAPA, and different roughage:concentrate ratios, and Cabral et al (2008), who evaluated different forages. These same authors, utilizing corn silage, reported slightly greater efficiencies than the results obtained in the current study.…”
Section: Resultscontrasting
confidence: 70%
“…In another study, Silva et al (2007) evaluated diets with Tifton hay and different protein sources for cattle, reporting mean values ranging from 5.14 to 5.55 g/100 g DM.…”
Section: Resultsmentioning
confidence: 99%
“…No entanto, os animais alimentados apenas com feno apresentaram menores consumos de PB (Tabela 2). Apesar do consumo baixo de proteína pelos animais, a fermentação da fibra alimentar e o crescimento microbiano foram adequados, pois os teores de amônia mantiveram-se acima de 5 mg/dL (Silva et al, 2007), teor mínimo preconizado por Satter & Slyter (1974) para a atividade dos microrganismos ruminais. Dutra et al (1997), utilizando ração com farelo de soja (3,8% PDR) e farelo de glúten de milho-60 + farelo de soja (0,8% PDR), encontraram consumos de PB de 0,25 e 0,23% PV, respectivamente, que não diferiram entre as fontes de N de diferentes degradabilidades.…”
Section: Resultsunclassified
“…Indicam ainda uma pequena deficiência dietética de proteína degradável no rúmen (Dutra et al, 1997;Ladeira et al, 1999;Ribeiro et al, 2001). Estes resultados podem ser comprovados também pelas menores concentrações de N-NH 3 no líquido ruminal dos animais recebendo esta dieta (Silva et al, 2007), refletindo utilização mais eficiente de N no rúmen dos animais recebendo esta dieta.…”
Section: Resultsunclassified
See 1 more Smart Citation